Dysphagia in neuromyelitis optica spectrum disorder and myelin oligodendrocyte glycoprotein antibody disease as a surrogate of brain involvement?. (12th January 2021) - Pawlitzki, Marc; Ahring, Sigrid; Rolfes, Leoni; Dziewas, Rainer; Warnecke, Tobias; Suntrup‐Krueger, Sonja; Wiendl, Heinz; Klotz, Luisa; Meuth, Sven G.; Labeit, Bendix
Abstract: Background and purpose: Neuromyelitis optica spectrum disorder (NMOSD) and myelin oligodendrocyte glycoprotein antibody disease (MOGAD) are demyelinating disorders that typically affect the optic nerves and the spinal cord. However, recent studies have demonstrated various forms of brain involvement indicating encephalitic syndromes, which consequently are included in the diagnostic criteria for both. Swallowing is processed in a distributed brain network and is therefore disturbed in many neurological diseases. The aim of this study was to investigate the occurrence of oropharyngeal dysphagia in NMOSD and MOGAD using flexible endoscopic evaluation of swallowing (FEES) as a surrogate parameter of brain involvement. Methods: Thirteen patients with NMOSD and MOGAD (mean age 54.2 ± 18.6 years, six men) who received FEES during clinical routine were retrospectively reviewed. Their extent of oropharyngeal dysphagia was rated using an ordinal dysphagia severity scale. FEES results were compared to a control group of healthy individuals. Dysphagia severity was correlated with the presence of clinical and radiological signs of brain involvement, the Expanded Disability Status Scale (EDSS) and the occurrence of pneumonia. Results: Oropharyngeal dysphagia was present in 8/13 patients, including six patients without other clinical indication of brain involvement. Clinical or subclinical swallowing impairment was significantly more severe in patients with NMOSD and MOGAD compared to the healthy individuals ( p = 0.009) and correlated with clinical signs of brain involvement ( p = 0.038), higher EDSS ( p = 0.006) and pneumonia ( p = 0.038). Conclusion: Oropharyngeal dysphagia can occur in NMOSD and MOGAD and might be associated with pneumonia and disability. FEES may help to detect subclinical brain involvement.